Learning from West African storytellers - Bakare, Ayomide; Ciancarini, Paolo; Farina, Mirko; Kruglov, Artem; Okonicha, Ozioma; Smirnova, Marina; Succi, Giancarlo (Frontiers in Computer Science, 2023)
Traditional West African communities did not make use of writing for thousands of years and yet their legends, customs, beliefs and knowledge were effectively transmitted across several generations. How did they manage to accomplish this? What can we learn from their storytellers? How can these lessons be applied to software products? These are all questions that this paper attempts to answer. Perhaps if we fully understand how they operated, then we can target our written communication to the activities where it is needed instead of spreading writing across plenty of tasks as it is currently. To achieve this, we performed an analysis of the two domains: West African oral storytelling and software development and found similarities, then selected some key elements from oral storytelling and explained how they can have relevance in software development. The theme directly encompasses diversity and inclusion by bringing into software engineering a perspective of a region where its literacy research is scarcely being explored. The study found that traditional oral storytelling can provide insights into effective communication and audience engagement, and identified four ways in which software development can be compared to oral storytelling. The study also found that certain elements of storytelling, such as audience relationship, story structure, parables and proverbs, and community relaxation and support, can be applied to writing tasks in software development.